Measuring the Digital Economy. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
Digitalization encompasses a wide range of new applications of information technology in business models and products that are transforming the economy and social interactions. Digitalization is both an enabler and a disruptor of businesses. The lack of a generally agreed definition of the 'digital economy' or 'digital sector' and the lack of industry and product classification for Internet platforms and associated services are hurdles to measuring the digital economy. This paper distinguishes between the 'digital sector' and the increasingly digitalized modern economy, often called the 'digital economy,' and focuses on the measurement of the digital sector. The digital sector covers the core activities of digitalization, ICT goods and services, online platforms, and platform-enabled activities such as the sharing economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet